Syngnathus rostellatus in the Sylt Rømø bight in 2020 - Johannes J Rick; Birgit Hussel; Petra Kadel; Ragnhild Asmus; Karen Helen Wiltshire (PANGAEA, 2021)
Due to changing temperature regimes in the North- and the Wadden Sea, a fish survey in the Sylt Rømø bight (SRB) was established in 2007 for at least ten years. The aim is to investigate the Wadden Sea fish fauna with special interest in changes of migration behavior, species composition and feeding habits. Seven stations are sampled monthly inside the SRB. Two additional stations, one outside the bight, one close to the Danish border are sampled as references four times a year. For sampling a mini bottom trawl, total length 17 m, trawl opening 7 m, height 3 m with a mesh size of 36 mm in the wings, 16 mm in the mid part and 6 mm in the cod end is used. At every station one haul in the water column and another at the bottom are sampled, for 15 minutes at a speed of approximately 2 knots. The data will help to give a more detailed picture of food chains and energy flows inside the Wadden Sea.
In: Asmus, Harald; Hussel, Birgit; Kadel, Petra; Asmus, Ragnhild; Rick, Johannes J; Wiltshire, Karen Helen (2020): Fish monitoring in the Sylt Rømø bight (2007 et seq) [dataset publication series]. Alfred Wegener Institute - Wadden Sea Station Sylt, PANGAEA, https://doi.org/10.1594/PANGAEA.911261